A longitudinal study of cognitive insight and cortical thickness in first-episode psychosis - Buchy, Lisa; Makowski, Carolina; Malla, Ashok; Joober, Ridha; Lepage, Martin (Schizophrenia research, 2018)
Among individuals with psychosis, those with poor cognitive insight (lower Self-Reflectiveness, higher Self-Certainty) show volumetric reductions in cortical structure. We evaluated whether changes in cognitive insight are associated with progressive changes in cortical structure in first-episode psychosis (FEP) and control subjects. Beck Cognitive Insight Scale ratings and magnetic resonance imaging scans were acquired at baseline for 130 FEP and 52 controls, 59 FEP and 28 controls at 1-year, and 53 FEP and 20 controls at 2-years. Cortical thickness was computed across scans and analyzed with linear mixed models. At baseline, groups did not differ on Self-Reflectiveness or Self-Certainty. At baseline, higher Self-Reflectiveness significantly correlated with thinner right occipital cortex in FEP, and higher Self-Certainty was significantly negatively correlated with cortical thickness in left posterior cingulate in controls. Longitudinal analysis showed that Self-Reflectiveness and Self-Certainty did not change over time in either group. Interestingly, the lack of change in cognitive insight aligned with longitudinal cortical thickness results, where no interaction effects were seen with cortical thickness between time and either Self-Reflectiveness or Self-Certainty. Exploratory analyses with a reduced threshold found that in FEP, across all time-points, higher Self-Certainty associated with thinner cortex in left posterior cingulate/precuneus. Results suggest that the posterior cingulate may be a common neural correlate for Self-Certainty in FEP and non-clinical subjects.